Endophytic mycobiota associated to plants of Vaccinium corymbosum L. in Cañete valley- Perú - Leon, Betsabe; Astete, Almendra; Mattos, Luz; Arévalo, Enrique (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Endophytic fungi (EF) are microorganisms that live asymptomatically within plant tissues. They can confer benefits to the plant as inducers of resistance to pests and diseases, tolerance to abiotic factors, plant growth promoters and mycoparasites of pathogens. This study aimed to isolate, identify, and determine occurrence frequency of endophytic fungi in stems and leaves of blueberry plants collected from ten farms in Lima and Ica Region, Peru. Productive branches of 39 healthy plants were sampled. For the isolation of EF, 702 tissue sections were disinfected and transferred to Petri dishes with potato dextrose agar (PDA) medium, and reproductive structures were induced for identification. A total of 134 EF strains were isolated successfully. Nine genera were identified (Trichoderma, Aspergillus, Alternaria, Ulocladium, Cladosporium, Fusarium, Nigrospora, Lasiodiplodia and Stemphylium). EF occurrence frequency varied greatly between organs, being in leaves more frequent than the stems; likewise, the genera Alternaria and Cladosporium were the most frequent and with most colonized in plant tissues, while Aspergillus, Ulocladium and Lasiodiplodia were the least frequent. These strains could be useful to control plant diseases and, therefore, of great interest in sustainable agriculture.